Drug interaction of efavirenz and midazolam: efavirenz activates the CYP3A-mediated midazolam 1′-Hydroxylation in vitro - Keubler, Anja; Weiß, Johanna; Haefeli, Walter E.; Mikus, Gerd; Burhenne, Jürgen (Drug metabolism and disposition, 2012)
CYP3A4 and CYP3A5 are the most important drug-metabolizing enzymes. For several drugs, heteroactivation of CYP3A-mediated reactions has been demonstrated in vitro. In vivo data suggested a possible acute activation of CYP3A4-catalyzed midazolam metabolism by efavirenz. Therefore, we aimed to investigate the effect of efavirenz on the in vitro metabolism of midazolam. The formation of 1′-hydroxymidazolam was studied in pooled human liver microsomes (HLM) and recombinant human CYP3A4 and CYP3A5 (rCYP3A4 and rCYP3A5) in the presence of efavirenz (0.5, 1, and 5 μM). Product formation rates (Vmax) increased with increasing efavirenz concentrations (∼1.5-fold increase at 5 μM efavirenz in HLM and ∼1.4-fold in rCYP3A4). The activation in rCYP3A4 was dependent on cytochrome b5, and the activating effect was also observed in rCYP3A5 supplemented with cytochrome b5, where Vmax was ∼1.3-fold enhanced. Concomitant inhibition of CYP3A activity with ketoconazole in HLM abolished the increase in the 1′-hydroxymidazolam formation rate, further confirming involvement of CYP3A. The results of this study represent a distinct acute activation of midazolam metabolism and support the in vivo observations. Moreover, only efavirenz, but not its major metabolite 8-hydroxyefavirenz, was responsible for the activation. The increase in 1′-hydroxymidazolam formation may have been caused by binding of efavirenz to a peripheral site of the enzyme, leading to enhanced midazolam turnover due to changes at the active site.